The Albuquerque Meeting, 8-11 October 2015. (Technology & Culture, 2016)
The article discusses the fifty-eighth annual meeting of the Society for the History of Technology (SHOT) which was held at the Hotel Albuquerque in Albuquerque, New Mexico on October 8-11, 2015, and it mentions the contributions of event organizers such as Kevin Borg, William Storey, and Lars Heide. Session events addressing topics such as computer hacking, the history of space exploration, and the Soviet Union's technology during the interwar period are also assessed.